My Characters. Reflections of a Documentary Film Director - Dashuk, Volha (Kultura-Społeczeństwo-Edukacja, 2016)
The author, being a documentary film director, analyzes an important part of a documentarian’s work – relations with characters. She describes this unique kind of a bond that develops between a director and his or her protagonists. The process of coming closer to characters is investigated in detail and the strategies of gaining the characters’ trust are named. The issues what problems the director experiences on the way and how they can be solved are addressed. The questions of the director’s responsibility regarding the characters and unexpected provocations on their side, as well as of mutual protagonist-director influence are brought up. All matters referred to in this article are illustrated by examples from the director’s professional life.